A new 1p36.13‐1p36.12 microdeletion syndrome characterized by learning disability, behavioral abnormalities, and ptosis. Issue 6 (1st April 2020) - Aagaard Nolting, Line; Brasch‐Andersen, Charlotte; Cox, Helen; Kanani, Farah; Parker, Michael; Fry, Andrew E.; Loddo, Sara; Novelli, Antonio; Dentici, Maria Lisa; Joss, Shelagh; Jørgensen, Joan P.; Fagerberg, Christina R.
Abstract: Two 1p36 contiguous gene deletion syndromes are known so far: the terminal 1p36 deletion syndrome and a 1p36 deletion syndrome with a critical region located more proximal at 1p36.23‐1p36.22. We present even more proximally located overlapping deletions from seven individuals, with the smallest region of overlap comprising 1 Mb at 1p36.13‐1p36.12 (chr1:19077793‐20081292 (GRCh37/hg19)) defining a new contiguous gene deletion syndrome. The characteristic features of this new syndrome are learning disability or mild intellectual disability, speech delay, behavioral abnormalities, and ptosis. The genes UBR4 and CAPZB are considered the most likely candidate genes for the features of this new syndrome. Abstract : A new microdeletion syndrome in 1p36 is characterized by learning disability, behavioral abnormalities and ptosis.